Processing of Green Composites - Rakesh, Pawan Kumar; Singh, Inderdeep (Materials Horizons: From Nature to Nanomaterials, 2019)
This book is a collection of chapters focusing on green composite materials. The selection of natural fibers and polymer matrix materials, and the bonding between them forms an essential aspect of this book. The book discusses the chemical treatment of natural fibers and their compatibility with different matrix materials. The growing applications of composites in every day life ranging from automobiles to aerospace are also discussed. The book highlights the importance of processing of natural fiber reinforced composite materials to enhance their mechanical strength and performance. The contents of this book will be beneficial for students, researchers and industry professionals working on composite materials. .